Otimização do desempenho de enrolamentos de máquinas elétricas através de algoritmo de enxames de partículas multiobjetivo - Martins, François de Souza (2022)
The present work demonstrates the optimization of the operation of electric machine windings. The parameters under study are the magnetomotive force and the end winding leakage inductance, obtained from the discrete distribution of conductors in the airgap. A multi-objective particle swarm metaheuristic optimization routine was proposed. The developed application is capable of generating the airgap conductor distribution for different machine configurations (single or poly-phase, single or double-layer, integral or fractional slots, full or shortened pitch, with the presence of empty slots, etc.), as well as the magnetomotive force curves and the end winding leakage inductance. Taking as an optimal winding the one that presents, simultaneously, less harmonic distortion of the magnetomotive force and less leakage inductance, the optimization by multi-objective particle swarm algorithm was used to obtain the optimal electrical machine parameter configuration.